2017
DOI: 10.3310/hta21220
|View full text |Cite
|
Sign up to set email alerts
|

What carcinoembryonic antigen level should trigger further investigation during colorectal cancer follow-up? A systematic review and secondary analysis of a randomised controlled trial

Abstract: Background Following primary surgical and adjuvant treatment for colorectal cancer, many patients are routinely followed up with blood carcinoembryonic antigen (CEA) testing. Objective To determine how the CEA test result should be interpreted to inform the decision to undertake further investigation to detect treatable recurrences. Design Two studies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…ctDNA is more likely to be detected in patients with more advanced stage cancer, whether with methylation or mutation markers. Studies have shown that ctDNA positivity increases with CRC stage, through measuring proportions of cases that are ctDNA positive with methylated BCAT1/IKZF1 (Pedersen et al, 2015; Symonds et al, 2018), KRAS mutations (Shin et al, 2017), and with a panel of mutations ( KRAS, BRAF, EGFR, PIK3CA ) (Kidess et al, 2015). Measurement of the quantitative levels of ctDNA also increase with stage, as shown in a study that measured ctDNA levels of methylated SEPT9 and SHOX2 (Bergheim et al, 2018).…”
Section: Search Criteria and Overviewmentioning
confidence: 99%
“…ctDNA is more likely to be detected in patients with more advanced stage cancer, whether with methylation or mutation markers. Studies have shown that ctDNA positivity increases with CRC stage, through measuring proportions of cases that are ctDNA positive with methylated BCAT1/IKZF1 (Pedersen et al, 2015; Symonds et al, 2018), KRAS mutations (Shin et al, 2017), and with a panel of mutations ( KRAS, BRAF, EGFR, PIK3CA ) (Kidess et al, 2015). Measurement of the quantitative levels of ctDNA also increase with stage, as shown in a study that measured ctDNA levels of methylated SEPT9 and SHOX2 (Bergheim et al, 2018).…”
Section: Search Criteria and Overviewmentioning
confidence: 99%
“…The Follow-up after Colorectal Surgery (FACS) trial concluded that CEA testing should not be used as a single triage test. 39 The correlation between follow-up elevated serum CEA levels and recurrence to distant sites has been reported, and is the greatest for hepatic metastases compared to metastases at other organs or structures. 24,40 The results of the current study strengthen this finding.…”
Section: Discussionmentioning
confidence: 99%
“…To compare with other tumor markers, the widely accepted colorectal cancer biomarker carcino‐embryonic antigen (CEA) has a 41% to 97% sensitivity, which is somewhat higher, and a 52% to 100% specificity, which is comparable to that of S‐100B . A recent study revealed that 1.5% of all CEA measurements from curatively treated patients with stage I‐III colorectal cancer ultimately led to recurrence detection . As with S‐100B, a normal CEA level does not exclude recurrent disease …”
Section: Discussionmentioning
confidence: 99%
“…19 A recent study revealed that 1.5% of all CEA measurements from curatively treated patients with stage I-III colorectal cancer ultimately led to recurrence detection. 20,21 As with S-100B, a normal CEA level does not exclude recurrent disease. 22 Tumor markers can be used in cancer detection and diagnosis, but are mainly used in follow-up to detect recurrent disease in an early phase.…”
Section: Costsmentioning
confidence: 99%